Factors affecting multifunctional teams in innovation processes - Xin Shen (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2002)
Structuring the innovation process and managing multifunctional teams is a basic prerequisite successful innovation. A well-structured process gives the possibility to implement effective multifunctional teamwork. Meanwhile, multifunctional teamwork helps to optimise and accomplish the innovation process. Organizational support is necessary to achieve effective teamwork. Designing or changing the organizational structures for multifunctional collaboration is an important issue. Changing the system of performance measurement and setting up a multifunctional organizational culture gives employees strong signals that multifunctional integration is encouraged.
urn:nbn:de:gbv:830-opus-1500
Keywords: 650; product development; innovation process; multifunctional team